Flower‐Like NiS2/WS2 Heterojunction as Polysulfide/sulfide Bidirectional Catalytic Layer for High‐Performance Lithium−Sulfur Batteries (Small 11/2023). Issue 11 (15th March 2023) - Wang, Jinyi; Zhou, Ling; Guo, Daying; Wang, Xueyu; Fang, Guoyong; Chen, Xi'an; Wang, Shun
Abstract : Bidirectional Catalytic Conversion A flower‐like nickel sulfide/tungsten sulfide heterojunction material are developed to promote the bidirectional catalytic conversion of polysulfides in lithium‐sulfur batteries. Specifically, in article number 2206926, Daying Guo, Xi'an Chen, and co‐workers adapt nickel sulfide to regulate the electronic structure of tungsten sulfide, causing the heterojunction simultaneously serve as electron acceptor/donor, improving the bidirectional reaction kinetics of polysulfides.